Association of age and gender in patients undergoing pulp capping- a retrospective study - K, KIRAN; K, DR.SOWMYA.; NARAYAN, DR.VIVEK (The journal of contemporary issues in business and government, 2021)
Pulp capping is a procedure commonly performed to preserve the vitality of the pulp in teeth with lesion approximating or involving the pulp. Careful case selection is critical as its successful clinical outcome depends on several factors. The aim of the study was to evaluate the association between patients' age and gender with pulp capping. The study was a retrospective analysis done in a university set up. Data of patients who underwent pulp capping were collected by evaluating the patient records and tabulated. Data was imported to IBM SPSS version 20 software and statistical analysis done. The frequency of pulp capping was higher in the age group of 16 to 30 years, however there was no significant association between pulp capping in different age groups (Chi square: p value- 0.358). Gender of the patients had no significant association with pulp capping (Chi square: p value-0.93) although pulp capping was performed more frequently in males. Within the limitations of the study, it was concluded that different age groups and gender did not affect the treatment planning for pulp capping.